S. Baranova, O. Rozhenko. Problem of transformations in translation of english-language national anthems. - S. Baranova; O. Rozhenko (Philological Treatises, 2020)
This article deals with the translation aspect of English-language national anthems as texts of ideological discourse. The paper is aimed at analyzing characteristic translation transformations which are performed while translating the national anthems of the USA, Canada, and Ireland into Ukrainian. The aim of the research implies conducting the detailed analysis of the conveyance of the external (rhythm, rhyme) and internal (content, ideological concepts, images) poetic matrix in the Ukrainian translations. The most frequently used lexical-semantic (concretization, modulation, generalization), grammatical (conversion), syntactic (integration, change of word order) transformations are determined. The main ideological concepts (the True North, the Star-Spangled Banner, the soldier’s song) of each national anthem are found out; they are completely represented in the Ukrainian poetic translations which function as texts of ideological discourse.